2021
DOI: 10.3390/sym13112223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molding Technology on Thermal Efficiencies and Pollutant Emissions from Household Solid Fuel Combustion during Cooking Activities in Chinese Rural Areas

Abstract: Resident combustion of solid fuel has been widely acknowledged as a high potential for pollutant reduction. However, there is a marked asymmetry between more pollutant emission and less burned volatiles of biomass and coal in the combustion process. To study the solid fuel optimum combustion form in a household stove, both the pollution reduction and energy efficient utilization of crop straws and coals were investigated. Taking the molding pressure and clay addition ratio as variable process conditions, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In order to reduce environmental pollution, Chinese government has encouraged application of biomass briquette and coal briquette in residential combustion since 2014. Bio-coal briquettes, a mixture of biomass and coal, have been recommended as suitable alternative solid fuel because of their low pollutant emissions and high thermal efficiency [35,36]. During bio-coal briquette combustion, the drawbacks of biomass and coal complement each other; therefore, better combustible qualities can be achieved [37].…”
Section: Research Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce environmental pollution, Chinese government has encouraged application of biomass briquette and coal briquette in residential combustion since 2014. Bio-coal briquettes, a mixture of biomass and coal, have been recommended as suitable alternative solid fuel because of their low pollutant emissions and high thermal efficiency [35,36]. During bio-coal briquette combustion, the drawbacks of biomass and coal complement each other; therefore, better combustible qualities can be achieved [37].…”
Section: Research Contributionmentioning
confidence: 99%
“…In addition, biomass that scatters in bio-coal briquette is burnt before coal and numerous pores are formed. Such a structure facilitates the transfer of mass and heat, reduces the formation of oxygen-depleted zones, and hence declines emissions of pollutants [35,36]. Therefore, there is tremendous significance for exploration of bio-coal briquette on BrC emissions based on the hazards and impacts mentioned above.…”
Section: Research Contributionmentioning
confidence: 99%
“…The measurement method for TEs adopted in our research has been reported in previous publications [23,26]. CO, NO x , SO 2 (Thermo Scientific; 43i, and 42i for CO, NO X , and SO 2 , respectively; Thermo Fisher Scientific Inc, Waltham, MA, USA), and CO 2 (GC-0012; Gas Sensing Solutions Ltd., Cumbernauld, Scotland) were tested using online gas analyzers.…”
Section: Test Proceduresmentioning
confidence: 99%
“…A kettle with 2.0 kg of room temperature water was employed to test the TEs each time. A second kettle with the same amount of room temperature water replaced the previous one when the water temperature reached 90 • C in case water vapor ran into the flue piper [23,26]. The kettles were exactly the same, and the initial water temperature was kept constant every time.…”
Section: Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation